The contest of the reproductive hormone in men' blood living in conditions of anthropogenic pollution - Nikolay Georgievich Belyaev; Juliya Anatol'yevna Yagupova; Natalia Nikolaevna Okolito (Наука. Инновации. Технологии)
A comparative analysis was carried out of the hormonal status of men of reproductive age living in regions with varying anthropogenic load. The control group included men in the age of 19-22 years old, living in the city of Stavropol. Men in the course of their professional activity, in contact with nitrogen oxide and ammonia were contained in two groups. Men in the age of 19-22 years have made the first experimental (control) group and men aged 23-44 years -were in the second group. The men, working in a chemical company are recorded with high levels of estradiol in many times higher than the physiological norm. The containing of testosterone, a lu-teinizing hormone and follicle hormone were within the physiological range, but was significantly lower in comparison with those of men who live in areas with less intensity human contamination. It is marked the cumulative effect of the complex action of chemical factors. Men working in the chemical company for a long time were recorded a marked increase in estradiol and the decline of testosterone levels.